Addressing the Cosmetic Approach to Rising Poverty Levels in Nigeria - Akinsiku, Daniel Akinwolire (Kashere Journal of Politics and International Relations, 2025)
In recent times, Nigeria has been plunged into an unprecedented economic crisis characterised by an increase in the inflationary level, decreased economic growth, the loss of jobs, and an increase in the poverty rate. These incidents were occasioned by the negative impact of the removal of fuel subsidies, as announced by President Asiwaju Bola Ahmed Tinubu during his inaugural speech on May 29, 2023, and subsequently the floating of the currency. This situation led to widespread dissatisfaction among the population, calling for decisive action by the government to address the various shades of economic issues being faced by the country. This paper sought to evaluate the efficacy of the measures implemented by the Nigerian government aimed at addressing increasing poverty levels as a result of the stern economic measures pursued by President Asiwaju Bola Ahmed Tinubu’s administration. The paper adopts a qualitative approach in its data collection, and analysis of the findings was done through content analysis. The findings of this paper revealed that despite the numerous interventions, poverty levels continue to rise, suggesting a probable mismatch between the policies and the potential strategies to mitigate poverty. The paper concludes that the various policies and strategies aimed at addressing poverty in the country, which appear to focus only on the short term, are cosmetic measures that have led to a cycle of ineffective poverty alleviation outcomes. The paper suggests providing measurable palliatives to vulnerable groups, promoting agricultural incentives, encouraging manufacturing and resuscitating local refineries to reduce fuel dependency.